(untitled) (Hematology Meeting Reports, 2009)
The majority of cancer patients do not die from their primary tumor but from disseminated tumor cells traversing through the body to form distant metastases.1,2 As one of the initial steps in this process, tumors secrete the vascular permeability factor VEGF that prompts the neighboring microvasculature to become permeable to fibrinogen and to other plasma proteins.3,4 Extravasated plasma-derived fibrinogen is rapidly cleaved by the serine protease thrombin to generate cross-linked fibrin, a process which also constitutes the final step in the intravascular blood coagulation cascade.5-8